2014
DOI: 10.1155/2014/286493
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Applications of Procalcitonin in Pediatrics: An Advanced Biomarker for Inflammation and Infection—Can It Also Be Used in Trauma?

Abstract: Background. Procalcitonin is a small molecular peptide that has gained increased support as an adjunct diagnostic marker of infection in the adult population; the concordant body of evidence for the use of procalcitonin in pediatric populations is far less complete. Objectives. Our objective is to review the current evidence supporting the utilization of procalcitonin in children in a variety of clinical scenarios including SIRS, sepsis, burns, and trauma and to identify existing knowledge gaps. Methods. A tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 23 publications
3
8
0
Order By: Relevance
“…Therefore, our findings suggest that BAL under fiberoptic bronchoscopy can effectively relieve heavy bleeding, small airway interference, restore breathing, increase the oxygen content in the blood, and help to reduce cerebral edema, thereby accelerate the recovery. At the same time, the effectiveness of treatment in the observational group was significantly compared to the control group, suggesting that BAL can effectively improve the treatment effectiveness, which is consistent with the conclusions of previous studies (20).…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, our findings suggest that BAL under fiberoptic bronchoscopy can effectively relieve heavy bleeding, small airway interference, restore breathing, increase the oxygen content in the blood, and help to reduce cerebral edema, thereby accelerate the recovery. At the same time, the effectiveness of treatment in the observational group was significantly compared to the control group, suggesting that BAL can effectively improve the treatment effectiveness, which is consistent with the conclusions of previous studies (20).…”
Section: Discussionsupporting
confidence: 90%
“…Some studies conclude that PCT is a more effective marker of infection compared with C-reactive protein because it peaks sooner and has a higher positive likelihood of infection. 5,6 Studies also suggest that PCT is elevated in patients with medullary thyroid cancer and lung cancer with neuroendocrine components and liver metastases. 7,8 A recent study suggested that patients with a PCT of 1.2 ng/mL most likely have a bacterial infection and that antibiotics should be started immediately; however, other studies fail to support this threshold.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, blood samples of 30 children with acute trauma were investigated, in which 23% developed sepsis and the PCT peaked at day 2. PCT at day 2 was an independent predictor of the development of sepsis in children (39,40).…”
Section: Acute Systemic Inflammatory Markersmentioning
confidence: 99%